The perfect guests - Rous, Emma (Berkley, 2021)
"The USA Today bestselling author of The Au Pair returns with another delicious, twisty novel--about a grand estate with many secrets, an orphan caught in a web of lies, and a young woman playing a dangerous game. 1980: Beth Soames is fourteen years old when a kind couple finds her playing the violin at her orphanage's yearly fund-raiser. The Averills take her home with them to Raven Hall, a rambling manor on the Norfolk coast. There she runs wild with their daughter, Nina, and they become fast friends. At times, Beth even dreams she's truly part of the family...until she's asked to take part in what seems like a harmless game--and nothing is ever the same. Present day: Sadie Langton is an actress struggling to make ends meet when she lands a well-paying gig attending a weekend party. Her anonymous employer sends her a suitcase of clothing, a dossier of the role she is to play, and instructions--it's strange, but she needs the money, and when she sees the stunning manor she'll be staying at she can't resist the chance. In person, Raven Hall is even grander than she'd imagined--even with the damage from a fire decades before--but the walls seem to have eyes. As day turns to night, there is something off about the glamorous guests who arrive, and as the game she is meant to be leading begins, it becomes chillingly apparent their unseen host has plans for all of them...including her"--